Persistent high prevalence of pulmonary tuberculosis in a resource-limited setting: threat to India's TB Free campaign. (9th December 2021) - Bhat, Jyothi; Sharma, Ravendra K; Yadav, Rajiv; Mishra, Prashant; Nigam, Samridhi; Lingala, Mercy Aparna; Rao, V G
Abstract: Background: Tuberculosis (TB) is a major public health problem among Saharia, a particularly vulnerable tribal group residing in remote rural areas in central India. This article presents the findings from the baseline survey among Saharias and provides comprehensive prevalence data of pulmonary TB (PTB) in this marginalised community. Methods: A community-based cross-sectional PTB prevalence survey was carried out during January–May 2019 in selected villages using multistage stratified cluster sampling. All eligible adults (≥15 years of age) were screened for the symptoms of PTB. Sputum samples were collected and processed for microscopy and culture for Mycobacterium tuberculosis . Results: A total of 20 114 eligible individuals were screened for symptoms of PTB. Among these, 3001 (14.9%) individuals reported at least one PTB symptom and sputum was collected from 2890 (96.3%) individuals. Among these, 273 (9.4%) were bacteriologically positive for PTB. The overall prevalence was 1357 per 100 000 population. Conclusions: The findings indicate that TB continues to be a major health problem in this marginalised community despite large investments by the government for TB control. This emphasizes the need to look into the causes and barriers in implementation of the TB elimination programme in the community, especially in view of India's TB elimination goal by 2025.